Self-Esteem and Fixed Price in Islamic Law (A Critical Study of the Pesuke Tradition among the Nobles of the Sasak Tribe of Lombok) - Zaenudin Mansyur (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2021)
The Sasak aristocracy in Lombok is still very passionate about carrying out the pesuke tradition. Although, the pesuke practice did not infrequently cause various conflicts between the prospective bride and groom's families. For instance, when the prospective bride's family sets the pesuke value that is too high, which can burden the groom's family. In contrast, religion forbids us to burden and encourages us to work together, help, and ease each other to create a happy and prosperous family in the world to the hereafter. Therefore, this study aims to examine how the perspective of Islamic law on the concept of self-esteem and fixed price in the pesuke tradition. The results showed that the motivation of the Sasak aristocratic community in setting a high pesuke value so that the public still respected their communal identity. In addition, another reason in determining the fantastic value of pesuke is to make it a fixed price in a marriage with melaik, meruput, or merugul systems. Therefore, the groom's family must pay this Pesuke as a ransom to restore the bride's family's dignity. Meanwhile, according to Islamic law, the pesuke tradition as a form of maintaining self-respect and fixed price should be a tolerable case for the creation of a peaceful and prosperous marriage because of the emergence of mutual willingness and pleasure between the two parties, by the essence of pesuke, namely mutual desire.